Fix, Develop, Keep! - Laitinen, Markku Antero (Qualitative and Quantitative Methods in Libraries; Vol 8 No 2 (2019): June 2019 Issue, 2019)
The Net Promoter Score (NPS) introduced by Fred Reichheld in 2003, is widely used in the business to measure the customers’ loyalty to the enterprise by enquiring their willingness to recommend the product, the service or the enterprise as a whole to their friends or colleagues. In the library world, the NPS has been used in a large scale in the National Library of Finland since 2016 on the National Finna Service of Finnish libraries, archives and museums. The three user surveys of Finna in the years 2016, 2018 and 2019 produced altogether 95,647 responses indicating a growing trend of user satisfaction as measured by the NPS. Following the idea of counting the NPS, dividing the responses to the survey in three groups: the Detractors (the most critical responses), the Passives (the neutral responses) and the Promoters (the most positive responses), the most critical points of development as well as the success factors were identified. On the basis of the surveys, measures basing on the most critical points of development were made after each survey. The NPS is included in the new standard ISO 21248:2019 (Quality assessment for national libraries).